2021
DOI: 10.3390/ijms22157838
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Cancer Targeted Therapy: Nodal and Cripto-1 as Attractive Candidates

Abstract: The transforming growth factor beta (TGF-β) signaling is fundamental for correct embryonic development. However, alterations of this pathway have been correlated with oncogenesis, tumor progression and sustaining of cancer stem cells (CSCs). Cripto-1 (CR-1) and Nodal are two embryonic proteins involved in TGF-β signaling. Their expression is almost undetectable in terminally differentiated cells, but they are often re-expressed in tumor cells, especially in CSCs. Moreover, cancer cells that show high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 110 publications
(117 reference statements)
0
4
0
1
Order By: Relevance
“…NODAL is an embryonic protein involved in TGF-b signaling and is highly expressed in various cancers. Cancer cells with high levels of NODAL displayed a more aggressive phenotype in vitro, while in vivo was associated with a poorer prognosis in several human cancers, highlighting it as a potential target and marker for targeted cancer therapy (70)(71)(72). Previous studies have also identified a novel link between OXT and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…NODAL is an embryonic protein involved in TGF-b signaling and is highly expressed in various cancers. Cancer cells with high levels of NODAL displayed a more aggressive phenotype in vitro, while in vivo was associated with a poorer prognosis in several human cancers, highlighting it as a potential target and marker for targeted cancer therapy (70)(71)(72). Previous studies have also identified a novel link between OXT and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Nodal’s role in embryogenesis, Activin/Nodal signaling maintains pluripotency in stem cells through induction of Nanog and other cell cycle factors ( Pauklin and Vallier, 2015 ). Cripto-1 is similar to Nodal in that it is an embryonic protein involved in TGF-β signaling ( Arboretto et al, 2021 ). Both Cripto-1 and Nodal have minimal expression in terminally differentiated cells, but are often re-expressed in CSCs and in a dose-dependent manner can trigger more aggressive phenotypes and worsened prognosis for several cancer-subtypes ( Arboretto et al, 2021 ).…”
Section: Signaling Pathways Linked To Cancer Stem Cellsmentioning
confidence: 99%
“…Cripto-1 is similar to Nodal in that it is an embryonic protein involved in TGF-β signaling ( Arboretto et al, 2021 ). Both Cripto-1 and Nodal have minimal expression in terminally differentiated cells, but are often re-expressed in CSCs and in a dose-dependent manner can trigger more aggressive phenotypes and worsened prognosis for several cancer-subtypes ( Arboretto et al, 2021 ).…”
Section: Signaling Pathways Linked To Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se cree que son las células iniciadoras del cáncer, así como el origen de las recaídas. Otra característica difundida en las CSC, pero no limitada a ellas, es la reactivación de algunas vías de señalización embriogénicas que son fundamentales para las células madre "normales" 174 . Esto suele deberse a la expresión aberrante de algunas proteínas implicadas en vías de señalización que suelen estar activas en las células embrionarias.…”
Section: Papel De La Vía Nodal En Ccrunclassified